2020
DOI: 10.1039/c9dt04908h
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Fe2O3 coatings on carbon nanotube structures for supercapacitors

Abstract: The combination of carbon nanotubes with transition metal oxides can exhibit complementary charge storage properties for use as electrode materials for next generation energy storage devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In addition, the assembled asymmetric supercapacitor CNTs@NiCo‐LDH||ZIF‐8 derived carbon can provide a high energy density of 37.38 Wh/kg at a power density of 800 W/kg and maintain 90.22% capacity after 5200 cycles. Yu et al 87 formed Fe 2 O 3 conformal coating on vertically aligned CNTs by atomic layer deposition. It is found that iron oxide coating increases the regional capacitance, but too thick (30 nm) coating reduces the active area and electrochemical properties.…”
Section: Binary Complexesmentioning
confidence: 99%
“…In addition, the assembled asymmetric supercapacitor CNTs@NiCo‐LDH||ZIF‐8 derived carbon can provide a high energy density of 37.38 Wh/kg at a power density of 800 W/kg and maintain 90.22% capacity after 5200 cycles. Yu et al 87 formed Fe 2 O 3 conformal coating on vertically aligned CNTs by atomic layer deposition. It is found that iron oxide coating increases the regional capacitance, but too thick (30 nm) coating reduces the active area and electrochemical properties.…”
Section: Binary Complexesmentioning
confidence: 99%
“…Ferrocene and its simple derivatives have been frequently used as a source of iron 197 or iron oxides during the preparation of Fe 2 O 3 nanoparticles 198 and bulk or surface-modified composite materials for sensing, 199 electronics 200 and catalysis, 201 whereas ferrocene itself is frequently used as a precursor of single-walled carbon nanotube (SWCNT) growth catalysts. 202 Ionic ferrocene derivatives ( e.g.…”
Section: Applications Of Ferrocene and Ferrocene Derivativesmentioning
confidence: 99%
“…The lowest R ct observed in Ru@a-CNTs is possibly attributed to (i) increase in the interfacial surface area resulted by acid treatment, which is supported by the result of the Brunauer–Emmett–Teller (BET) measurement shown in Figure S8 and Table S2, and (ii) facilitation of electron transfer owing to pseudocapacitive redox reactions of Ru NPs . At the low-frequency region, all curves are linear lines with high slopes, which are typically shown in the capacitive behavior of porous carbon electrodes without diffusion limitation. …”
Section: Resultsmentioning
confidence: 63%